FGFR2/STAT3 Signaling Pathway Involves in the Development of MMTV-Related Spontaneous Breast Cancer in TA2 Mice - Du, Jiaxing (Front Oncol, 2020)
The Tientsin Albino 2 (TA2) mouse has a high incidence of spontaneous breast cancer (SBC) in the absence of external inducers or carcinogens. The initiation of SBC is related to mouse mammary tumor virus (MMTV) infection and pregnancy. Pathologic analysis showed that breast cancer cells in TA2 mice are triple negative. Our previous study confirmed that fibroblast growth factor receptor 2 (FGFR2) expression increased in SBC tissue compared to that in their corresponding normal breast tissues of TA2 mice. The present study focused on the function of the FGFR2/STAT3 signaling pathway in the initiation of SBC. In this study, the expression of FGF3, FGFR2, STAT3, p-STAT3(Tyr705), and p-STAT3(Ser727) was detected in serum and normal mammary gland tissues of TA2 mice with different number of pregnancies and SBC. The proliferation, invasiveness, and migration abilities of MA-891 cells from TA2 SBC were compared before and after cryptotanshinone and Stattic treatment. Transient siRNA transfection was used to detect the invasiveness, and migration abilities to avoid the off-targets effects. Downstream protein expression of STAT3 was also detected in MA-891 cells and TA2 xenografts from MA-891 inoculation. In addition, STAT3 expression was analyzed in 139 cases of human breast cancer including 117 cases of non-triple negative breast cancer (non-TNBC) (group I) and 22 cases of triple-negative breast cancer (TNBC) (group II). Results of our study confirmed that MMTV-LTR amplification, and FGFR2, p-STAT3(Tyr705), p-STAT3(Ser727) expression increased with the number of pregnancies in the breast tissue of TA2 mice and were the highest in SBC. Serum FGF3 expression of SBC was higher than it of TA2 mice with different number of pregnancies. After STAT3 was inhibited, the abilities of proliferation, invasiveness, and migration in MA-891 decreased and the expression levels of STAT3, p-STAT3(Ser727), p-STAT3(Tyr705), Bcl2, cyclin D1, and c-myc in MA-891 and animal xenografts were also down-regulated. In human breast cancer, STAT3 expression was significantly higher in TNBC than that in non-TNBC. Our results showed that the FGFR2/STAT3 signaling pathway may be related to SBC initiation in TA2 mice. Inhibition of STAT3 can decrease proliferation, invasiveness, and migration in MA-891 cells and the growth of TA2 xenografts.